A low-frequency magnetic Field regulates Monascus pigments synthesis via reactive oxygen species in M. purpureus. (November 2019) - Liao, Qian; Liu, Yingbao; Zhang, Jialan; Li, Li; Gao, Mengxiang
Graphical abstract: Highlights: The pksPT gene is an important Monascus pigments biosynthesis gene in M. purpureus . Low-frequency magnetic field (LF-MF) improved the MPs and reduced CTN yield. The reactive oxygen species (ROS) production was changed by the LF-MF. LF-MF changed three key indicators related to ROS. LF-MF changed gene expression of related to MPs and CTN synthesis and ROS. Abstract: Monascus pigments (MPs) are secondary metabolites of Monascus purpureus . The gene ( pksPT ) encoding a polyketide synthase (PKS) involved in MPs biosynthesis was knocked out. The mutant (Δ pksPT ) exhibited decreased MPs production and increased citrinin (CTN) levels. Low-frequency magnetic field (LF-MF) improved the MPs yield of M. purpureus (WT) and significantly reduced the production of CTN in both WT and Δ pksPT in the middle and late stages of fermentation. This result was verified by measuring the gene expression of the MPs synthesis genes and the CTN synthesis genes. The MPs yield was significantly affected and the colonies were smaller in size with increasing of H2 O2 concentration in WT. The reactive oxygen species (ROS) production was activated by the LF-MF at the early stage of fermentation and decreased significantly with the extension of fermentation time in WT. The LF-MF affected superoxide dismutase (SOD) activity, total glutathione (T-GSH) production, the ratio of oxidized to reduced glutathione (GSSG/GSH), and SOD and GST gene expression in WT and Δ pksPT . The results showed that the PKS could participate in the response of M. purpureus to LF-MF stress, and LF-MFs could regulate MP biosynthesis via ROS.